Direct mass measurements above uranium bridge the gap to the island of stability - Block, Michael; Ackermann, D.; Blaum, Klaus; Droese, C.; Dworschak, Michael Gerhard; Eliseev, Sergey; Fleckenstein, T.; Haettner, E.; Herfurth, F.; Heßberger, F. P.; Hofmann, S.; Ketelaer, J.; et al. (Nature, 2010)
Present knowledge of the binding energy of the heaviest nuclides is based solely on the detection of their decay products. This paper reports the first direct mass measurements of the trans-uranium nuclides 252-254No (nobelium, atomic number 102), which will be important for mapping the predicted 'island of stability' of superheavy elements.
Gesehen am 15.02.2023